2009
DOI: 10.1016/j.yjmcc.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insulin signaling accelerates cardiac mitochondrial dysfunction after myocardial infarction

Abstract: Diabetes increases mortality and accelerates left ventricular (LV) dysfunction following myocardial infarction (MI). This study sought to determine the impact of impaired myocardial insulin signaling, in the absence of diabetes, on the development of LV dysfunction following MI. Mice with cardiomyocyte-restricted knock out of the insulin receptor (CIRKO) and wild type (WT) mice were subjected to proximal left coronary artery ligation (MI) and followed for 14 days. Despite equivalent infarct size, mortality was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 64 publications
5
35
1
4
Order By: Relevance
“…Furthermore, RCR can be used as a quality assurance marker and can identify changes in coupling resulting from experimental or pathological interventions 5 . Well-coupled permeabilized murine cardiac preparations yield an RCR between 3-6 depending on the incubation solution utilized 1,8,9 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Furthermore, RCR can be used as a quality assurance marker and can identify changes in coupling resulting from experimental or pathological interventions 5 . Well-coupled permeabilized murine cardiac preparations yield an RCR between 3-6 depending on the incubation solution utilized 1,8,9 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…In the heart, deletion of the insulin receptor promotes oxidative stress and diminishes mitochondrial respiratory capacity 34. Consistently, cardiomyocyte‐specific loss of the insulin receptor accelerates cardiac mitochondrial dysfunction and thereby worsens left ventricular function and survival in mice with MI 5. Therefore, it is reasonable to postulate that the development of cIR in pressure‐overloaded hearts was an important trigger of mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Studies in genetic models have shown that impaired cardiac insulin signaling has an adverse impact on mitochondrial and contractile function 5, 6. However, whether cardiac insulin action is affected in clinically relevant models of HF is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(71,72) Recently, Sena et al (73) used cardiomyocyte-restricted insulin receptor knock out (CIRKO) mice to investigate possible mechanisms responsible for this. In a model of proximal coronary artery ligation to induce infarction, they followed changes in the heart over a 14 day period.…”
Section: Gsk-3 and Myocardial Cell Death Or Cell Survivalmentioning
confidence: 99%